Partnership Management in Industrial Work Practice of Hospitality Expertise Program at SMKN 3 Tanjungpandan and SMKN 1 Sijuk, Belitung Regency - Yuli Yulianti; Setya Raharja (Indonesian Interdisciplinary Journal of Sharia Economics (IIJSE), 2025)
This study explores partnership management in the Industrial Work Practice program for the hospitality expertise track at SMKN 3 Tanjungpandan and SMKN 1 Sijuk in Belitung Regency. It focuses on four key management functions planning, organizing, implementation, and supervision while identifying supporting and inhibiting factors in the partnership process. The goal is to offer strategic insights to strengthen’s effectiveness in enhancing students’ skills aligned with industry needs (DUDIKA). Using a qualitative descriptive approach, the study involved school leaders, program heads, supervising teachers, and DUDIKA partners. Data were gathered through interviews, observations, and document analysis, and validated using source and method triangulation. The findings show that both schools follow a structured partnership framework supported by formal agreements (MoUs), curriculum synchronization, and student skill development. Active collaboration with DUDIKA is central, with effective communication helping to address challenges such as scheduling conflicts, student readiness, and resource limitations. Strategies like flexible scheduling, increased parental involvement, and supervisor support have contributed to program success. Key success factors include strong industry relations, competent teachers, student preparedness, and mentoring from partner hotels.